ANALISIS PENGARUH RETURN ON EQUITY, CURRENT RATIO, DEBT RATIO, OPERATING LEVERAGE DAN ASSET GROWTH TERHADAP BETA SAHAM SYARIAH DI BURSA EFEK INDONESIA - Nugroho, Wahyudi (Magister Manajemen, Fakultas Ekonomika dan Bisnis Undip, 2010)
Since July 2000 PT. Bursa Efek Jakarta (BEJ) and PT. Danareksa Investment Management (DIM) launch the Jakarta Islamic Index (JII) which consist of all emitents with business activity complied to syariah law. Risk of investment, consist of systematic risk and non systematic risk, is also inevitable in securities trading of syariah stock. In investment analysis, non systematic risk is often neglected because of itâ€™s characteristics that can be omitted by diversification, therefore the only risk which needs more attention is the systematic risk. This study specifically analyse the effect of return on equity, current ratio, debt ratio, operating leverage and asset growth variables on beta of syariah stock as the measurement of systematic risk in Bursa Efek Indonesia (BEI) in 2005 â€“ 2008. Samples used in this study consist of companies which consistantly listing on the Jakarta Islamic Index (JII) within the period of the study. The result of five research hypothesis using multiple regression method shows that only asset growth variable has significant effect on beta of syariah stock at 5% significant effect, while return on equity, current ratio, debt ratio and operating leverage variables statistically proven that they do not have any significant effect on beta of syariah stocks.Â